2013
DOI: 10.1021/jp400366k
|View full text |Cite
|
Sign up to set email alerts
|

Reactivity of First-Row Transition Metal Monocations (Sc+, Ti+, V+, Zn+) with Methyl Fluoride: A Computational Study

Abstract: The gas-phase reactivity of methyl fluoride with selected first-row transition metal monocations (Sc(+), Ti(+), V(+), and Zn(+)) has been theoretically investigated. Our thermochemical and kinetics study shows that early transition-metal cations exhibit a much more active chemistry than the latest transition metal monocation Zn(+). The strong C-F bond in methyl fluorine can be activated by scandium, titanium, and vanadium monocations yielding the metal fluorine cation, MF(+). However, the rate efficiencies var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
34
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(38 citation statements)
references
References 43 publications
3
34
1
Order By: Relevance
“…It was shown that the strong C F bond in methyl fluoride can be activated by scandium, titanium, and vanadium monocations yielding the metal fluorine cation, MF + . However, the rate efficiencies vary dramatically along the period 0.73 (Sc), 0.91 (Ti), and 0.028 (V) in agreement with the experimental observation [2]. A detailed computational study on the equilibrium geometries, stability and vibrational frequencies of a series of Sc(CO) n (n = 1-7), Sc(CO) 7 − and Sc(CO) 6 3− has been reported using density functional theory functionals and the coupled cluster (single-point) method with 6-311 + G(3df) basis set.…”
Section: Homoleptic Compoundssupporting
confidence: 88%
See 2 more Smart Citations
“…It was shown that the strong C F bond in methyl fluoride can be activated by scandium, titanium, and vanadium monocations yielding the metal fluorine cation, MF + . However, the rate efficiencies vary dramatically along the period 0.73 (Sc), 0.91 (Ti), and 0.028 (V) in agreement with the experimental observation [2]. A detailed computational study on the equilibrium geometries, stability and vibrational frequencies of a series of Sc(CO) n (n = 1-7), Sc(CO) 7 − and Sc(CO) 6 3− has been reported using density functional theory functionals and the coupled cluster (single-point) method with 6-311 + G(3df) basis set.…”
Section: Homoleptic Compoundssupporting
confidence: 88%
“…Divalent ytterbium compounds containing the tris(dimethylsilyl)methyl ligand have been described. The potassium precursors KC(SiHMe 2 ) 3 and [KC(SiHMe 2 ) 3 TMEDA] 2 were synthesized by deprotonation of the hydrocarbon HC(SiHMe 2 ) 3 with benzylpotassium. The divalent ytterbium compounds Yb[C(SiHMe 2 ) 3 ] 2 L (L = 2THF, TMEDA) were prepared from YbI 2 and 2 equiv.…”
Section: Homoleptic Compoundsmentioning
confidence: 99%
See 1 more Smart Citation
“…17 It is important to stress that the results reported in this work do provide a full mechanistic prediction about the studied processes in the sense that we fill the gap between quantum calculations and kinetics prediction (directly comparable with experimental data) by employing an appropriate theoretical kinetics model. In other words, the predicted rate constants should be, according to our previous work, [13][14][15][16] in reasonable good agreement with the corresponding experimental values when available.…”
Section: Introductionsupporting
confidence: 74%
“…Calculations suggested that these reactions seem to proceed through a ''harpoon''-like mechanism, but further work, including other metal cations, was necessary to support the validity of the mechanistic findings reported. Recently, and, in order to get insight into the selectivity and mechanism of carbon-fluorine bond activation of fluoromethane, we have extended our research to different first-row transition metal monocations (Sc + , Ti + , V + , Zn + ), 15 and main fourth-period monocations (Ga + , Ge + , As + , Se + ). 16 In the case of first-row transition metal monocations we found theoretical evidence for a ''harpoon''-like mechanism for the fluorine-atom abstraction process that operates via electron transfer from the transition metal cation to the CH 3 F substrate in the transition structure.…”
Section: Introductionmentioning
confidence: 99%